RISIKO RIWAYAT PAJANAN PESTISIDA TERHADAP UKURAN TUBUH BAYI BARU LAHIR - Dayu Yunita Putri; Ratih Sari Wardani (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background : Brebes Regency in the highest of utilizing pesticides in Indonesia. But theoverwhelming utilizing pesticides have potentially for causing many adverse effects which can make damage for the human health and the environment, especially for the pregnant women who work and live in that area. Pesticides exposure potentially make some adverse effect for fetal growth during the pregnancy and causing the abnormal of pregnant outcome such as head circumference, birth length and birth weight are less than the normal standard.Method: This type of research was explanatory and used cohort retrospective apporoach.The samples of this research consist of 60 gave birth mothers from three different villages in Tanjung District there were Tanjung, Lemahabang and Sengon. The independent variables were risk of pesticides exposure, times of work and periods of work. The dependent variables were the new born baby body size consist of head circumference, birth length and birth weight. Data analyzed by Chi Square, independent sample t test and Mann Whitney.Result: There was no correlation between the risk of pesticides exposure history and headcircumference p=0,068 but there was significant difference of head circumferences average in exposure and not exposure group p=0,016. There was no correlation between risk of pesticides exposure history and birth length p=0,103, but there was significant difference of birth length average in exposure and not exposure group. There was significant difference of birth weight average in exposure and not exposure group p=0,019. There was no correlation between times of work and head circumference p=0,288. There was no correlation between times of work and birth length p=0,088 and also there was no significant difference of birth weight in exposure and not exposure group p=0,278. This research also reveal there was no correlation between period of work and head circumference p=0,288. There was no correlation between period of work and birth length p=0,088 and also there was no significant difference of birth weight in exposure and not exposure groups p=0,278.Conclusion: There were no correlation between risk of pesticides exposure history and headcircumference, birth length and birth weight. There were no correlation between times of work and head circumference, birth length and birth weight. There were no correlation between period of work and head circumference, birth length and birth weight, but this research reveal there were significant difference of head circumference and birth weight in exposure and not exposure groups.